A topology preserving cluster‐based channel assignment for wireless mesh networks. (8th May 2014) - Athota, Kavitha; Negi, Atul
Summary Wireless Mesh Networks (WMN) with multiple radios and multiple channels are expected to resolve the capacity limitation problem of simpler wireless networks. However, optimal WMN channel assignment (CA) is NP complete, and it requires an optimal mapping of available channels to interfaces mounted over mesh routers. Acceptable solutions to CA must minimize network interference and maximize available network throughput. In this paper, we propose a CA solution called as cluster‐based channel assignment (CBCA). CBCA aims at minimizing co‐channel interference yet retaining topology through non‐default CA. Topology preservation is important because it avoids network partitions and is compatible with single‐interface routers in the network. A 'non‐default' CA solution is desired because it uses interfaces over different channels and reduces medium contention among neighbors. To the best of our knowledge, CBCA is a unique cluster‐based CA algorithm that addresses topology preservation using a non‐default channel approach. The main advantage of CBCA is it runs in a distributed manner by allowing cluster heads to perform CA independently. CBCA runs in three stages, where first the WMN nodes are partitioned into clusters. The second stage performs binding of interfaces to neighbors and third stage performs CA. The proposed algorithm improves over previous work because it retains network topology and minimizes network interference, which in turn improves available network throughput. Further, when compared with two other CBCA algorithms, CBCA provides better performance in terms of improved network interference, throughput, delay, and packet delivery ratios when tested upon network topologies with various network densities and traffic loads. Copyright © 2014 John Wiley & Sons, Ltd.